(untitled) (Research, Society and Development, 2025)
Known for its box office success and popularity among teenage audiences for debating from a philosophical and futuristic perspective the advancement of technologies associated with the government control of a city subdivided into a system of factions, Veronica Roth’s Divergent Saga addresses current themes that serve as a bridge for dialogue between young people and teachers on discussions in various areas of knowledge, including complex problems existing in the evolution of medical education and the challenges of fragmented and mechanical medical practice. This article aims to present an experience report of using an active teaching methodology, Role-playing, associated with the fantasy scenario of the Divergent saga to problematize medical hyperspecialization in analogy to the development of the faction system. It is associated with a narrative literature review, with strategic debates of the discussion stages of youth literature inserted in the resolution of a complex clinical case in a specialty outpatient clinic context, discussing issues such as the creation and unbridled encouragement of subspecialized academic leagues contributing to the maintenance of the hegemonic biomedical model and which strengthens the hospital-centric and fragmented view of the human person, hindering clinical reasoning from a biopsychosocial perspective and aiming at integrated and person-centered care. In this way, it makes a critical analogy of the view of the divergent in the saga as a threat to the system for not fitting into just one specific group, in analogy to the process of invisibility and inferiorization of family medicine as a comprehensive medical specialty.